2020
DOI: 10.1371/journal.pone.0233592
|View full text |Cite
|
Sign up to set email alerts
|

Gradual positive and negative affect induction: The effect of verbalizing affective content

Abstract: In this paper, we study the effect of verbalizing affective pictures on affective state and language production. Individuals describe (Study I: Spoken Descriptions of Pictures) or passively view (Study II: Passively Viewing Pictures) 40 pictures for the International Affective Picture System (IAPS) that gradually increase from neutral to either positive or negative content. We expected that both methods would result in successful affect induction, and that the effect would be stronger for verbally describing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Thus, after finishing the intervention, the compensatory group felt worse than the iso group. The finding that significant between-group differences were only observed concerning negative affect is in line with evidence that it is easier to induce negative affect than positive affect (e.g., Out et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…Thus, after finishing the intervention, the compensatory group felt worse than the iso group. The finding that significant between-group differences were only observed concerning negative affect is in line with evidence that it is easier to induce negative affect than positive affect (e.g., Out et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…Two Ph.D students and two master students from the research team evaluated the usability of the standardized processed pictures, while referring to relevant studies by Out et al (2020) to develop usability evaluation rules. First, image content is complete and clear, without watermarks or text logos.…”
Section: Experiments 1: Expert Evaluation Of Image Materialsmentioning
confidence: 99%
“…A second study indicated that inclusion of taboo words in a picture-word interference task, changes the effect of non-taboo emotion words during speech production (White and Abrams, 2021). Expanding the horizon to more natural dialogue, recent results suggest that mood can influence the alignment in referring expressions produced in an interactive context (Out et al, 2020). This new promising line of research is still in its infancy.…”
Section: Effects Of Mood On Language Production?mentioning
confidence: 99%